Investigation on the Effects of RAP Proportions on the Pavement Performance of Recycled Asphalt Mixtures - Ma, Xiang; Wang, Jiaqing; Xu, Yinyin (Frontiers in Materials, 2022)
In-plant hot mix recycling technology has been widely used in maintenance and reconstruction due to its good recycling performance. However, the utilization rate of recycled asphalt pavement (RAP) is still only 10–25%, resulting in excessive accumulation and landfilling of RAP materials, which fails to promote the sustainable value of RAP in recycling. Therefore, this paper comprehensively explores the pavement performance of AC-20 ordinary asphalt recycled mixture and AC-13 modified asphalt recycled mixture with different proportions of RAP. The pavement performance test includes the dynamic modulus, rutting, dynamic creep, semicircular bending, and freeze-thaw splitting tests. The results show that, with the increase of RAP content, the mechanical properties and high-temperature properties of the two types of recycled asphalt mixtures are improved, the low temperature properties and moisture susceptibility properties are enhanced first and then weakened, and the best performance is reached when RAP content is 20 and 40%, respectively. According to the entire pavement performance test results, the influence of RAP content on AC-13 recycled modified asphalt mixtures is relatively smaller than that of AC-20 normal recycled asphalt mixtures. The addition of rejuvenator can improve the low-temperature performance and moisture susceptibility of recycled asphalt mixtures to a certain extent, especially for AC-20 ordinary recycled asphalt mixture. Consequently, it is suggested to use AC-13 recycled modified asphalt mixture in the upper layer of road; the RAP content can reach 20%, and rejuvenator can be used to improve its moisture susceptibility and low-temperature performance. AC-20 ordinary recycled asphalt mixture can be used in the middle surface layer, and the RAP content can reach 40%, or using AC-13 recycled modified asphalt mixture, the RAP content can reach 50%.